IMPLEMENTASI PROGRAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR WILAYAH PONTIANAK KOTA - Irasandi, Yusi; Aunurrahman, Aunurrahman; Waruwu, Marinu; Asrori, M; Sartika, Rodi Putra (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study analyzed the implementation of a character education program at SD Negeri 24, Pontianak Kota District. The focus included the role of the principal, policy substance, communication strategies, implementation by teachers and students, and the achievement of program goals. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The findings revealed that: (1) the principal acted as a policy initiator through the flagship program “7 Habits of Great Indonesian Children,” collaboratively developed; (2) the character education policy integrated values such as religiosity, discipline, honesty, cooperation, independence, courage, creativity, and environmental awareness into various school activities; (3) program communication was effectively conducted through coordination meetings, WhatsApp groups, and school social media; (4) teachers and students actively participated as implementers through daily habituation and classroom learning; and (5) the program successfully fostered positive student behavior despite challenges in monitoring digital device usage. The study recommends maintaining implementation consistency, enhancing teacher capacity, and strengthening collaboration with parents to optimize character education in elementary schools.